Struktur, Kategori, dan Fungsi Sosial Petatah Petitih Minangkabau di Nagari Sianok IV Suku Kabupaten Agam - Nanda, Muhammad Irvan; Nasution, Muhammad Ismail (Universitas Negeri Padang, 2024)
This research is conducted to document the structure, categories, and social functions of Minangkabau proverbs at Nagari Sianok VI Suku Agam Regency. The aim of this research is to describe structure, categories, and social functions of Minangkabau proverbs at Nagari Sianok VI Suku Agam Regency. This research is a qualitative using a descriptive methods. The data were conducted by doing interview using recording sheers, voice recording device, and interview guideline. The results of this research is revealing 42 Minangkabau proverbs at Nagari Sianok VI Suku Agam Regency which have: physical structures (diction, imagery, figure of speech, typography, and concrete words); internal structures (themes, feelings, tones, and messages); categories (animals, plants, part of body, human, and nature); and social functions (educational tools, enforces and supervisors of norms, instruments for traditions and cultural institutions, and projection systems). This research concludes that Minangkabau proverbs have an influence on customs and normative values at Nagari Sianok VI Suku Agam Regency.